2020
DOI: 10.18231/j.ijodr.2020.036
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of common concerns of 2nd year post graduate students pursuing M.D.S In orthodontics and dentofacial orthopedics, due to the COVID-19 lockdown

Abstract: The fight against the novel coronavirus and the disruption in our daily routine and practise due to lockdown has been mentally exhausting especially for ambitious students pursuing higher studies. The lockdown period came in suddenly giving no chance to be prepared for the worst. Post-graduate students of Orthodontics and Dentofacial Orthopedics could be badly hit by this lockdown period disrupting the entire treatment course of patients undergoing orthodontic treatment, which needs monthly visits to the ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In the present study, the average age of the participants came out to be 29 years with ages ranging from 27 to 38 years and more than 70% of the students aged less than 30 while in the previous study which was conducted by Rodrigues lishoy the age range was 25 to 35 years and the average age of 30 years, that clearly states that the average age of trainees differs between the countries 14 .In this study, nearly a quarter i.e;22 (27.2%) of the participants reported that they attended a patient 2 months ago and a few of them also reported that they attended a patient a month ago i.e;4(4.9%) and 4 months ago i.e;4(4.9%). This long gap between appointments is seen because of the strict guidelines discussed by Sunjay Suri, where he discusses the implem-entation of clinical guidelines by many institutes.…”
mentioning
confidence: 40%
See 1 more Smart Citation
“…In the present study, the average age of the participants came out to be 29 years with ages ranging from 27 to 38 years and more than 70% of the students aged less than 30 while in the previous study which was conducted by Rodrigues lishoy the age range was 25 to 35 years and the average age of 30 years, that clearly states that the average age of trainees differs between the countries 14 .In this study, nearly a quarter i.e;22 (27.2%) of the participants reported that they attended a patient 2 months ago and a few of them also reported that they attended a patient a month ago i.e;4(4.9%) and 4 months ago i.e;4(4.9%). This long gap between appointments is seen because of the strict guidelines discussed by Sunjay Suri, where he discusses the implem-entation of clinical guidelines by many institutes.…”
mentioning
confidence: 40%
“…Related to resuming of work after COVID-19 lockdown also demands the health care workers to abide by new international guidelines of social distancing while not compromising the patient care which is quite challenging not only for dental even for every clinical specialty. However, it is thought to be more difficult in the domain of dentistry as the close contact with patients is mandatory for their clinical assessments and to carryout the dental pr-ocedures.A similar study was conducted by Rodrigues Lishoy for Indian postgraduate trainees 14 ,but there is a definitive difference in the training setups between Indian and Pakistani population and also the criteria for selection of the trainees, years of training and level of practice. Every aspect in both populations is somewhat different hence there is a possibility that there might be a difference between concerns and worries amongst the trainees.…”
mentioning
confidence: 81%